The Contribution of Online Peer-to-Peer Communication Among Patients With Adrenal Disease to Patient-Centered Care - Kauw, Dirkjan; Repping-Wuts, Han; Noordzij, Alida; Stikkelbroeck, Nike; Hermus, Ad; Faber, Marjan (JMIR Publications, 2015)
BackgroundAddison's disease and Cushing's syndrome are rare. The Dutch Adrenal Society offers an online forum for Dutch adrenal patients to meet and communicate. However, little is known about the added value such a forum has for the delivery of patient-centered care. ObjectiveOur aim was to analyze the purposes of online patient-to-patient forum conversations, within the context of patient-centered care. MethodsFor this study a consecutive sample of 300 questions ("threads") from the past 3.5 years was selected from the forum. The content of these patient-driven questions was analyzed based on the dimensions of patient-centeredness of the Picker Institute. This analysis was performed using ATLAS.ti. ResultsFrom the 390 questions analyzed, 80.8% (N=315) were intended to gain more information about the disease, the treatment, and to verify if other patients had similar complaints. To a much lesser extent (38/390, 9.7%), questions expressed a call for emotional support. Patients answered primarily by giving practical tips to fellow patients and to share their own experiences. ConclusionsOn an online patient forum for Cushing's syndrome and Addison's disease, patients appear to primarily gain knowledge and, to a lesser extent, emotional support from their peers. This experience-based knowledge has become a very important information source. As such, patients can make a substantial contribution to the creation of patient-centered care if this knowledge is integrated into the care provided by health care professionals.